Comparing Food Security Status between Sana'a and Taiz Governorates, Yemen - Masood, Muhammed; Al Mansoob, Muhammed (Journal of Amran University, 2021)
As a result of the conflict and aggression on Yemen since 2015, the majority of the Yemeni families have become unable to obtain and provide the food necessary for the continuation of life due to high prices, interruption of salaries, lack of job opportunities and deteriorating agricultural production, which in turn leads to a deterioration of the living conditions of the Yemeni families. Household food security is an important measure of well-being. Food security encompasses three dimensions: availability; access and utilization. Although it may not encapsulate all dimensions of poverty, the inability of households to obtain access to enough food for a productive healthy life is an important component of their poverty. Objective: The aim of study is to compare the Food Consumption Pattern (FCP) by Sana'a and Taiz Governorates (Govs), Yemen. Methods: Data was taken from a comprehensive survey that was conducted by the UNICEF during 2016 with a total sample of 921 and 1458 households in Sana'a and Taiz Govs, respectively. The FCP was measured by Household Dietary Diversity Score (HDDS). Descriptive statistics were used to calculate the consumption rate of Food Groups Consumed (FGC) by two Govs. Results: The findings show cereals, miscellaneous and sugar honey were the most frequently consumed in Taiz Gov, while oils, sugar honey and diary were the most frequently consumed in Sana'a Gov. Households in Sana'a Gov were more likely to consume meat and fruits than those in Taiz Gov. However, households in Taiz Gov were likely to consume seafood and eggs as compared to Sana'a households. Based on the income of household, more than 60% of households (in each Gov) were living on the three first income quintiles. The HDDS cut-off points were used to classify households into sufficient food or not sufficient. Approximately 21% of households in each Gov were consumed three or four or five FGC. Alternatively, HDDS were classified as average number of FGC. The findings indicate that about 62% of households were consumed at least one of seven FGC. Conclusion: HDDS based on average number of FGC should be suggested and lead to realistic results.